COP27 climate change conference: urgent action needed for Africa and the world. (18th October 2022) - Atwoli, Lukoye; Erhabor, Gregory E; Gbakima, Aiah A; Haileamlak, Abraham; Ntumba, Jean-Marie Kayembe; Laybourn-Langton, Laurie; Mash, Bob; Muhia, Joy; Mulaudzi, Fhumulani Mavis; Ofori-Adjei, David; Okonofua, Friday; Rashidian, Arash; et al.
Abstract : Wealthy nations must step up support for Africa and vulnerable countries in addressing past, present, and future impacts of climate change